2022
DOI: 10.1007/s10519-022-10112-z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Analysis of Imprinted Genes in the Cortex and Hippocampus of Cross-Fostered Mice Selectively Bred for Increased Voluntary Wheel-Running

Abstract: We have previously shown that high runner (HR) mice (from a line genetically selected for increased wheel-running behavior) have distinct, genetically based, neurobiological phenotypes as compared with non-selected control (C) mice. However, developmental programming effects during early life, including maternal care and parent-of-origin-dependent expression of imprinted genes, can also contribute to variation in physical activity. Here, we used cross-fostering to address two questions. First, do HR mice have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(29 citation statements)
references
References 145 publications
(224 reference statements)
3
26
0
Order By: Relevance
“…Although sex differences are not a primary question for this study, sex‐specific cross‐fostering effects were previously found within this cohort 1,67 and have been reported for numerous traits in other studies 89–91 . Therefore, we also considered sex‐specific cross‐fostering effects on DNA methylation only.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Although sex differences are not a primary question for this study, sex‐specific cross‐fostering effects were previously found within this cohort 1,67 and have been reported for numerous traits in other studies 89–91 . Therefore, we also considered sex‐specific cross‐fostering effects on DNA methylation only.…”
Section: Resultsmentioning
confidence: 95%
“…The goal of the present study was to quantify the DNA methylation patterns in the brains of one HR line of mice as compared with those from a non‐selected C line. Using a full factorial cross‐fostering paradigm, we have previously shown that the DNA methylation patterns for genes known to be genomically imprinted are altered in HR mice as compared with C, with additional imprinted genes also modified by maternal upbringing 67 . The paternally imprinted genes were particularly impacted, as HR mice had differential methylation patterns for Rasgrf1 in the cortex and Zdbf2 in the hippocampus compared with C mice.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed investigation of imprinted gene expression in the aging HCP was yet to be performed, despite previous association between imprinting methylation and hippocampal volume in aging 70 . Recent evidence suggested that imprints can be dysregulated by environmental insults during critical periods of embryonic/fetal development 71,72,73 with long-term consequences in tissue function and susceptibility to age-related diseases 25,26 . Whether imprinting in the brain is also susceptible to changes as a function of aging has not been addressed previously in a systematic way.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial selection provides a means to breed for a behavior of interest and use the resultant evolved organisms to test hypotheses about correlated evolution of other traits, including the brain and its function [Roderick et al, 1976;Rhodes and Kawecki, 2009;Garland et al, 2016]. Uncovering correlated responses to selection on behavior in real time (i.e., across generations) in a "top-down" fashion, from an altered behavior to potentially altered organs to tissues to pro-teins to DNA [Saul et al, 2017;Hillis et al, 2020;Nguyen et al, 2020;Latchney et al, 2022], may ultimately provide insights about specific genetic and epigenetic mechanisms that underlie individual and species differences in brain morphology and function, including the possibility of "multiple solutions" in response to selection [Garland et al, 2011a;Hillis and Garland, 2023]. For example, results of the present study support the idea that the human brain may have coadapted with the evolution of aerobically supported physical activity [Raichlen and Alexander, 2020] and that it indeed needs aerobic exercise to function optimally [Raichlen and Alexander, 2020].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Compared with C mice, HR mice build smaller nests when housed either with or without wheels [Carter et al, 2000]; HR mice make fewer turns in an open-field test [Bronikowski et al, 2001]; HR males have lower latencies to attack crickets in a test of predatory aggression [Gammie et al, 2003]; HR mice have reduced responsiveness to wheel-running rewards of shorter duration [Belke and Garland, 2007]; HR males spend more time immobile in the forced-swim test when wheel deprived, suggesting a predisposition for depression-like behavior or increased fear responsivity [Malisch et al, 2009a]; finally, HR males spent more time in the closed arms of an elevated plus maze, suggesting increased anxiety, increased fear responsivity or decreased risk-taking [Singleton and Garland, 2019]. The genetic and epigenetic basis for differences between the HR and C lines are an area of active investigation [Saul et al, 2017;Hillis et al, 2020;Nguyen et al, 2020;Latchney et al, 2022;Hillis and Garland, 2023].…”
Section: Introductionmentioning
confidence: 99%